(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
Castilla y León is a large region with an aging population. Cardiac surgical care is provided in the hospitals of Valladolid, Salamanca, and León. In this study, we aim to analyze the current state of care and explore potential areas for improvement. In Castilla y León, patient care shows significant differences in surgical waiting times and compliance with guaranteed time limits. The number of cases operated on per center is low, while the total number of professionals dedicated to cardiac surgery across the region is relatively high for the existing case volume. Clinical outcomes, based on key performance indicators, are good. It is necessary to reorganize care delivery based on efficiency and quality parameters.